1989
DOI: 10.1111/j.1600-0404.1989.tb03849.x
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities of mitochondrial enzymes in hereditary ataxias

Abstract: The activity of 7 mitochondrial enzymes, fumarase, NAD-malate dehydrogenase (MDH), citrate synthase (CS), valine dehydrogenase (VDH), succinate dehydrogenase (SDH), glutamate dehydrogenase (GDH), pyruvate dehydrogenase complex (PDHC) has been measured in platelet preparations from patients affected by Friedreich's ataxia (FA), dominant and non-dominant olivopontocerebellar atrophy (DOPCA, NDOPCA) and normal individuals. Significant decreases of GDH (P less than 0.01), PDHC (P less than 0.01), VDH (P less than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1
1

Year Published

1992
1992
2004
2004

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 41 publications
0
9
1
1
Order By: Relevance
“…At least one study suggests GDH deficiency may be an epiphenomenon. In this report, decreased activities of other mitochondrial enzymes were found but not to the same degree as that of GDH [Sorbi et al, 1989]. Finally, despite the findings of GDH deficiency, mutations of GDH have yet to be reported in OPCA.…”
Section: Olivopontocerebellar Atrophy-loss Of Gdh Activity Proposedcontrasting
confidence: 62%
“…At least one study suggests GDH deficiency may be an epiphenomenon. In this report, decreased activities of other mitochondrial enzymes were found but not to the same degree as that of GDH [Sorbi et al, 1989]. Finally, despite the findings of GDH deficiency, mutations of GDH have yet to be reported in OPCA.…”
Section: Olivopontocerebellar Atrophy-loss Of Gdh Activity Proposedcontrasting
confidence: 62%
“…Studies several years ago suggested that loss of mitochondrial enzyme activities including PDHC and KGDHC is commonly found in SCAs, 76,77 but extensive studies in patients whose defects have been defined at the gene level have not been done. The “toxin gain of function” of the Q n repeats may be mediated at least in part by aberrant transglutaminase‐catalyzed reactions.…”
Section: Kgdhc In Neurodegenerative Diseasesmentioning
confidence: 99%
“…Glutamate is also the precursor of GABA, an inhibitory neurotransmitter. Interestingly, a loss of GDH activity was reported in a multiple system atrophy condition called olivopontocerebellar atropy where GDH activity was decreased to a greater extent than other mitochondrial enzymes (52), suggesting that GDH is more sensitive to insults. Our study showed that it is, however, not inhibited by hydrogen peroxide from 10 -220 M concentration.…”
Section: Nadmentioning
confidence: 99%